2020
DOI: 10.18632/oncotarget.27590
|View full text |Cite
|
Sign up to set email alerts
|

Apolipoprotein A-I anti-tumor activity targets cancer cell metabolism

Abstract: Previously, we reported apolipoprotein A-I (apoA-I), the major protein component of high-density lipoprotein (HDL), has potent anti-melanoma activity. We used DNA microarray and bioinformatics to interrogate gene expression profiles of tumors from apoA-I expressing (A-I Tg +/-) versus apoA-I-null (A-I KO) animals to gain insights into mechanisms of apoA-I tumor protection. Differential expression analyses of 11 distinct tumors per group with > 1.2-fold cut-off and a false discovery rate adjusted p < 0.05, iden… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 83 publications
(105 reference statements)
0
1
0
Order By: Relevance
“…This may be due to a dose-Frontiers in Drug Delivery frontiersin.org dependent effect of ApoA-I. In addition, ApoA-I has been shown to alter cancer cell metabolism (Zamanian-Daryoush et al, 2020), and this may indirectly mediate the M1 phenotype observed in TAMs when tumor-bearing mice are administered ApoA-I. Thus, the negligible ApoA-I effect observed on the B16-F10 CM-educated RAW 264.7 macrophages could also be due to limitations of the in vitro model used in this study.…”
Section: Discussionmentioning
confidence: 99%
“…This may be due to a dose-Frontiers in Drug Delivery frontiersin.org dependent effect of ApoA-I. In addition, ApoA-I has been shown to alter cancer cell metabolism (Zamanian-Daryoush et al, 2020), and this may indirectly mediate the M1 phenotype observed in TAMs when tumor-bearing mice are administered ApoA-I. Thus, the negligible ApoA-I effect observed on the B16-F10 CM-educated RAW 264.7 macrophages could also be due to limitations of the in vitro model used in this study.…”
Section: Discussionmentioning
confidence: 99%